Kajian Psikolingusitik: Analisis Tuturan Tokoh Hendra dalam Film “My Idiot Brother” - Alya Hafizha; Mei Leani Olfah; Maulana Abdurrasid (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research examines the psychological aspects of language in the use of language in the character Hendra in the film My Idiot Brother. This research aims to analyze how the language of an individual with severe intellectual disabilities, especially idioty, is depicted through Hendra's speech patterns. The method used in this research is descriptive qualitative, by analyzing Hendra's verbal expressions in the film. Data collection was carried out by watching, recording and noting relevant speech examples from films. Research findings indicate that Hendra's language use reflects significant challenges in understanding complex instructions, producing clear speech, and interacting socially, which is consistent with characteristics of severe intellectual disability. This research contributes to understanding language difficulties in individuals with severe cognitive impairment, especially in relation to their ability to communicate and process information. The implications of this research are relevant for educational and therapeutic practice for individuals with similar conditions, emphasizing the importance of providing a supportive environment to meet their communication needs.